Comparison of the adults diagnosed and not diagnosed with anxiety disorder in terms of primary and secondary aptitudes of positive psychotherapy - Kok Eren, Hulya; Eryilmaz, Ali (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2019)
Objectives: The purpose of this study is to compare the adults diagnosed and not diagnosed with anxiety disorder in terms of positive psychotherapy formation. Methods: Participants of the study are 100 people diagnosed with anxiety disorder, and another 100 people who do not have any mental disorder. Positive Psychotherapy and Family Therapy Inventory, and Beck Anxiety Inventory were used to collect data. T-test and multivariate regression analysis were conducted for data analysis. Results: Regarding primary aptitudes, there are significant differences in terms of patience, relationship, love, and faith aptitudes. In study, a significant difference was found in terms of orderliness, cleanliness, kindness, honesty, obedience, justice and loyalty among the secondary and non-diagnosed groups. Diagnosed individuals have been found to use order, cleanliness, reliability, obedience, justice and loyalty more than non-diagnosed individuals. It is seen that individuals who have anxiety disorder are more patient than relatives without diagnosis are and use relational, love and faith ability more. It has been found that for the individuals diagnosed with anxiety disorder, all of primary aptitudes explains 32% of the total variance and all of secondary aptitudes explains approximately 30% of the total variance. It has been found that for non-diagnosed individuals all of primary aptitudes explains approximately 15% of the total variance and all of secondary aptitudes explains approximately 13% of the total variance. Discussion: Conducting similar studies in the future on individuals who are at different developmental periods, such as adolescence and old age, may be useful. In addition, various intervention programs can be performed using the perspective of positive psychotherapy for anxiety disorder treatment.
Keywords: anxiety disorder; psychotherapy; positive psychotherapy; DEPRESSION; EXERCISE; Psychiatry